Information empowerment of the Caribbean people: new thinking on old themes - Stephenson, Yvonne V. (ACURIL San JuanPR, 1993)
Explores the concept of empowerment in the context of the role of libraries and information services in the development of our Caribbean societies. Identifies information as a vital source of power in the strategies adopted for the development of the territories of the Region. Focuses on three problems which limit the pace of the process of empowerment. Offers some solutions.